2004
DOI: 10.1074/jbc.m407618200
|View full text |Cite
|
Sign up to set email alerts
|

Plasmodium Induces Swelling-activated ClC-2 Anion Channels in the Host Erythrocyte

Abstract: Intraerythrocytic growth of the human malaria parasite Plasmodium falciparum depends on delivery of nutrients. Moreover, infection challenges cell volume constancy of the host erythrocyte requiring enhanced activity of cell volume regulatory mechanisms. Patch clamp recording demonstrated inwardly and outwardly rectifying anion channels in infected but not in control erythrocytes. The molecular identity of those channels remained elusive. We show here for one channel type that voltage dependence, cell volume se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
79
2

Year Published

2005
2005
2013
2013

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(88 citation statements)
references
References 48 publications
7
79
2
Order By: Relevance
“…The IRC can be activated by forskolin in intact noninfected cells and in RBCs of cystic fibrosis patients; it is able to transport ATP, and its membership of the ATP binding cassette family of anion channel was suggested (17). It is probable that the Zn 2ϩ -sensitive channel belongs to the ClC-2 family, in keeping with the observations of Lang's group (16), who found by immunoblotting that ClC-2 protein is expressed in human RBCs. However, with regard to slow gating of ClC-2 channel (18), further experiments are clearly needed before definitely identifying the SCC-PSAC as a ClC-2 channel.…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…The IRC can be activated by forskolin in intact noninfected cells and in RBCs of cystic fibrosis patients; it is able to transport ATP, and its membership of the ATP binding cassette family of anion channel was suggested (17). It is probable that the Zn 2ϩ -sensitive channel belongs to the ClC-2 family, in keeping with the observations of Lang's group (16), who found by immunoblotting that ClC-2 protein is expressed in human RBCs. However, with regard to slow gating of ClC-2 channel (18), further experiments are clearly needed before definitely identifying the SCC-PSAC as a ClC-2 channel.…”
Section: Discussionsupporting
confidence: 68%
“…They showed that two of the anion conductances exhibit inward rectification and provided evidence that one of them is attributable to the chloride channel ClC-2, sensitive to cell volume and inhibited by Zn 2ϩ (16); the third conductance exhibits outward rectification. This group also found that conductances similar to each of those seen in infected cells can be activated in uninfected erythrocytes by oxidation (14).…”
mentioning
confidence: 99%
“…In contrast, another study found that Plasmodium vinckei induces a broad specificity, furosemide-sensitive pathway similar to PSAC and that it also upregulates the endogenous mouse RBC choline carrier (33). Electrophysiological studies of Plasmodium gallinaceuminfected chicken RBCs (36) and of Plasmodium bergheiinfected mouse RBCs (20) appear to support upregulation of endogenous channels, although achieved signal-to-noise ratios-calculated from solution compositions and reported seal resistances-were not adequate to rule out PSAC-like channels.…”
Section: ͼ Brmentioning
confidence: 86%
“…Similar currents recorded in Plasmodium berghei-infected mouse erythrocytes were absent from plasmodiuminfected Clcn2 -/-red cells [23]. The relationship between this current and the 80 pS outwardly rectifying anion conductance upregulated in red cells of cystic fibrosis patients [58] remains unclear.…”
Section: Possible Identity Of Mediator(s) Of the Dids-insensitive Animentioning
confidence: 71%
“…The pipette was backfilled with pipette solution containing 100 μM nystatin, then front-filled with nystatin-free pipette solution. In a typical experiment, attainment of a 20 GΩ cell-attached seal was followed within ∼3 min by a decrease in pipette resistance to ∼3 GΩ, indicative of transition from cellattached to whole cell configuration as first reported in frog erythrocytes [6] and subsequently in human [22] and mouse red cells [23].…”
Section: Nystatin-permeabilized Whole Cell Patch Clamp Of Red Cellsmentioning
confidence: 99%